Physicochemical Properties of Indoor Particulate Matter Collected on Subway Platforms in Japan - Chang-Jin Ma; Sigeo Matuyama; Koichiro Sera; Shin-Do Kim (Asian Journal of Atmospheric Environment, 2012)
This study was aimed to thoroughly estimate the characteristics of indoor particulate matter (PM) collected on subway platforms by the cooperative approach of semi-bulk and single particle analyses. The size-resolved PM and its number concentration were measured on the platform in a heavily traveled subway station in Fukuoka, Japan. Particle Induced Xray Emission (PIXE) and micro-PIXE techniques were applied to the chemical analyses of semi-bulk and single particle, respectively. There was the close resemblance of timely fluctuation between PM number concentration and train service on the third basement floor (B3F) platform compared to the second basement floor (B2F) and its maximum level was marked in rush hour. Higher number counts in large particles (>1 μm) and lower number counts in fine particles (<1 μm) were shown on the platform compared to an above ground. PM2.5 accounted for 58.2% and 38.2 % of TSP on B3F and on B2F, respectively. The elements that were ranked at high concentration in sizeresolved semi-bulk PM were Fe, Si, Ca, S, and Na. The major elements tending to have more elevated levels on B3F than B2F were Fe (4.4 times), Ca (17.3 times), and Si (46.4 times). Although concentrations were very low, Cr (11.9 ng m-3 on B3F, 2.4 ng m-3 on B2F), Mn (3.4 ng m-3 on B3F, 0.9 ng m-3 on B2F), and Pb (0.6 ng m-3 on B3F, 1.6 ng m-3 on B2F) were detected from PM2.5. Individual PM was nearly all enriched in Fe with Si and Ca. Classifying and source profiling of the individual particles by elemental maps and particle morphology were tried and particles were presumably divided into four groups (i.e., train/rail friction, train-rail sparking, ballast/abrasive, and cement).